Russian Court Interpretation of Legislative Measuresfor Advanced Training and (or) Professional Training of the Selected Employed Population Aged from 25 to 65 Years - ZAVGORODNIY, Alexander Vasilyevich; VASILYEV, Ilya Alexandrovich; DIVEEVA, Nelli Ivanovna; FILIPPOVA, Marina Valentinovna; KHARITONOV, Mikhail Mikhailovich (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).40, 2018)
In this article, we present the first generalization and analysis of decisions made by Russian courts of general jurisdiction from 2009 to 2016 for the application of provisions of the Labor Code of the Russian Federation, the Federal Law of November 21, 2011 No. 323-FZ ʼOn the fundamentals of protecting the health of citizens in the Russian Federationʼ, the Federal Law of July 3, 2016 No. 238-FZ ʼOn independent qualification assessmentʼ, the Federal Law of December 29, 2013 No. 273-FZ ʼOn education in the Russian Federationʼ, the Decree of the Government of the Russian Federation of October 28, 2013 No. 966 ʼOn licensing educational activitiesʼ adopted to fulfill the Decree of the President of the Russian Federation of May 7, 2012 No. 599 ʼAbout measures to implement the state policy in the sphere of education and scienceʼ in the field of advanced training and (or) professional training of employed population aged from 25 to 65 years. As a result, we have made several conclusions. Firstly, if periodical advanced training is a mandatory condition for admission to work (for example, for medical workers), then courts using separate methods of protecting rights of citizens (in particular, health care), should understand the consequences of these decisions. Secondly, the imposition of administrative sanctions in accordance with Part 3 of Article 19.20 of the Code of Administrative Offences due to the non-systematic increase in the professional level of educators recommends improving the algorithm for substantiating the gross violation of license requirements. Thirdly, the legal status of a person who has concluded an agreement on advanced training differs from that of an apprenticeship contract, and the guarantees for this person are not established by Articles 203-205 but rather Article 187 of the Labor Code of the Russian Federation. Therefore, courts should not qualify a contract on advanced training as an apprenticeship contract. Fourthly, if advanced training is not designated for employees as additional qualification and an employer does not have the duty to pay for this training, then the resolution of a possible dispute should be based on whether the employer's interest is realized or not. Fifthly, the impossibility of an employee to work should be objective and compulsory, which is assessed by the law enforcer based on the balance of rights and interests of both parties of the corresponding employment contract. Sixthly, the legal regulation of the independent assessment of working qualification requires its improvement and alignment with norms of the labor legislation of the Russian Federation.